Control over Crime Theory in the Rome Statute - Tavga Abbas Bustany; Sozan Rada Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The International Criminal Court has adopted the control over crime theory, to establish criminal responsibility for co-perpetration and indirect perpetration under article 25(3) (a) of the Rome Statute. As a result the court has been facing a wide range of criticism. It is important to clarify the notion of the control theory and make a reasonable interpretation of co-perpetration and indirect perpetration within the meaning of article 25(3) (a) according to the control theory for distinguishing between principles and accessories and secure the convection of multiple accused who in spite of being removed from the scene of the crime, control or mastermind its commission because they decide whether and how the offence will be committed.